PENDAMPINGAN REMAJA DESA MUNJUL DALAM MENGGUNAKAN MEDIA SOSIAL SECARA BIJAK DAN BERTANGGUNGJAWAB - Hartati, Tati (JURNAL PARAHITA ABDIMAS: Jurnal Pengabdian Masyarakat, 2020)
Community service activities carried out against the background of the phenomenon of the use of social media dilemmas among adolescents. On the one hand, adolescents are encouraged to master technology, on the other hand the use of social media has the potential for distortion that adversely affects social interaction. Assistance to adolescents in the use of social media aims to make them use wisely and responsibly and lead in a positive direction. Among other things to prevent the spread of hoaxes, slander, and posting that harm the people. The method used is assistance for adolescents who are members of Youth Organization. The material presented includes the role of adolescents in social life, various social media, how to use social media wisely and responsibly, and the application of Law No. 19 of 2016, regarding Information and Electronic Transactions. Evaluation results show that activities run smoothly and well and youth awareness of the importance of using social media wisely increases. Conclusion, youth assistance can increase the knowledge, understanding, and awareness of adolescents as responsible citizens.